A throughput estimation model under two-link concurrent communications with partially overlapping channels and its application to channel assignment in IEEE 802.11n WLAN. (2018) - Kwenga, Ismael Munene; Funabiki, Nobuo; Kuribayashi, Minoru; Sudibyo, Rahardhita Widyatra; Kao, Wen-Chung
Currently, the IEEE 802.11n wireless local-area network (WLAN) has been deployed world-wide due to flexibility and low costs. A key challenge in the WLAN deployment is to provide high data-rate under strong interferences due to the limited frequency channels. In WLAN, the adjacent channels are partially overlapped with each other, called partially overlapping channels (POCs) . Then, the optimal POC assignment to the access-points (APs) in WLAN using the mathematical model is important to improve the performance, particularly for usage of the channel bonding . In this paper, we propose the throughput estimation model extension for concurrent communications of two IEEE 802.11n links under interferences using POCs and the channel bonding, from extensive measurement results under a variety of conditions. Then, based on this model, we present the channel assignment extension in the active AP configuration algorithm for the elastic WLAN system, which dynamically optimises the topology depending on network conditions. For the evaluation, we verify the model accuracy through comparing estimated throughputs with measured ones under various conditions. On top of that, we confirm throughput improvements by adopting POCs from using merely orthogonal channels (OCs) in simulations and experiments in several topologies.